External Trade Bulletin of the ESCWA Region, Ninth Issue - Nations Unies (United Nations, 1998)
With statistics collected mainly at the national level, this Bulletin offers a comprehensive collection of data. Divided in three parts, part one gives summary tables on overall trade, trends and share of the region in total world trade. It also gives the import and export distributions of countries in the region according to the Standard International Trade Classification. Data in part two show the importance, network and structure of intraregional trade while part three provides data on the geographical distribution of trade of countries in the ESCWA region for the period 1992-2001.